ALZHEIMER’S DISEASE: CURRENT STATE OF KNOWLEDGE, DIAGNOSIS, TREATMENT, AND THE ROLE OF LIFESTYLE IN PREVENTION AND THERAPY - Wiktor Doroszuk; Jakub Hamouta; Dominika Nowak; Patrycja Długosz; Julia Konat; Magdalena Próchnicka; Michał Siwek; Adam Zarzycki; Jan Noskowicz; Jan Urban; Bartosz Skorupski; Natalia Strumnik (International Journal of Innovative Technologies in Social Science, 2025)
Background: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that leads to gradual memory loss, impaired thinking, and cognitive decline. It is characterized by the accumulation of amyloid plaques and neurofibrillary tangles in the brain, which damage nerve cells. As the disease progresses, patients lose the ability to function independently, resulting in complete dependence on care. Aim: This review aims to summarize current knowleadge about AD and evidence on dietary and lifestyle factors associated with AD Material and methods: A narrative review of recent literature was conducted using peer-reviewed articles published in PubMed and Google Scholar. Results: Based on a literature review, a proper balanced diet, rich in antioxidative and anti-inflammatory nutrients, may have a beneficial effect on the prevention of AD. Additionally, the diet should avoid highly processed foods, rich in saturated and trans fatty acids, and poor quality food, which may increase exposure to the consumption of pollution and toxins, such as heavy metals. Conclusions: Research, in addition to classical pharmacological treatment and modern imaging techniques, highlights the significant role of lifestyle changes—especially diet and regular physical activity—in the prevention and treatment of AD. Numerous studies indicate that maintaining a healthy, active lifestyle and a proper diet can significantly reduce the risk of developing cognitive impairments and dementia, including AD.